جودة الحياة الوظيفية وعلاقتها بالإبداع الإداري لدى الموظفات الإداريات في جامعة الأمير سلطان بالرياض - الشهري، مريم بنت محمد فضل (المركز العربى للتعليم والتنمية, 2021)
هدفت الدراسة إلى الكشف عن العلاقة بين جودة الحياة الوظيفية والإبداع الإداري لدى الموظفات الإداريات في جامعة الأمير سلطان بالرياض، من خلال تحديد درجة توافر أبعاد جودة الحياة الوظيفية والمتمثلة في: (الأمان والاستقرار الوظيفي، الأجور والمكافآت، الصحة والسلامة المهنية، فرص تطوير القدرات، الاندماج الاجتماعي في العمل، حرية التعبير والمشاركة)، وتحديد درجة ممارسة الموظفات الإداريات للإبداع الإداري، واستخدمت الدراسة المنهج الوصفي بأسلوبيه المسحي والارتباطي، والاستبانة أداة لها، وطبقت الدراسة على جميع الموظفات الإداريات بجامعة الأمير سلطان، والبالغ عددهن (149) إدارية، مستخدمة الحصر الشامل، وقد استجاب منهن (120) إدارية. وتوصلت الدراسة إلى عدد من النتائج، أبرزها ما يلي: أن درجة توافر أبعاد جودة الحياة الوظيفية بشكل عام في جامعة الأمير سلطان بالرياض جاءت بدرجة متوسطة، وبمتوسط حسابي (3.27 من 5)، وجاءت الأبعاد مرتبة تنازليا حسب توفرها كالتالي: (الاندماج الاجتماعي في العمل، الصحة والسلامة المهنية، حرية التعبير والمشاركة، فرص تطوير القدرات والتقدم الوظيفي، الأمان والاستقرار الوظيفي، الأجور والمكافآت)، كما أن درجة ممارسة الموظفات الإداريات بجامعة الأمير سلطان بالرياض للإبداع الإداري جاءت بدرجة مرتفعة، وبمتوسط حسابي (3.84 من 5). كما توصلت إلى وجود علاقة طردية موجبة ذات دلالة إحصائية عند مستوى الدلالة (α ≤ 0.05)، بين جودة الحياة الوظيفية والإبداع الإداري لدى الموظفات الإداريات في جامعة الأمير سلطان بالرياض. The study aimed to reveal the relationship between the quality of career life and administrative creativity among female administrative staff at Prince Sultan University in Riyadh, by determining the degree of availability of the dimensions of the quality of career life represented in: (career safety and stability, wages and rewards, occupational health and safety, capacity development opportunities, social integration at work, freedom of expression and participation), and determining the degree to which female administrative staff practice administrative creativity. The study used the descriptive approach with its survey and correlation methods, and the questionnaire as its tool. The study was applied to all the female administrative staff of Prince Sultan University, who are (149) administrative employees, using a comprehensive inventory, and 120 administrative employees responded. The study reached a number of results, most notably the following: The degree of availability of the dimensions of quality of career life in general at Prince Sultan University in Riyadh came to a medium degree, with an arithmetic average (3.27 out of 5). The dimensions were arranged in descending order according to their availability as follows: (social integration at work, occupational health and safety, freedom of expression and participation, capacity development opportunities, career advancement, career safety and stability, wages and rewards). The degree of administrative creativity of the administrative staff at Prince Sultan University in Riyadh came to a high degree, with an arithmetic average (3.84 out of 5). It also found that there is a positive a direct correlation with statistical significance at the significance level (α ≤ 0.05), between the quality of career life and administrative creativity among female administrative staff at Prince Sultan University in Riyadh.
Keywords: الحياة الوظيفية -- المؤسسات التعليمية -- الأداء الوظيفي -- القدرات الإبداعية -- الجودة الشاملة -- السعودية